Institutions and structures as barriers? A comparison of native‐born and immigrant unemployment durations across 12 European countries. (2nd May 2016) - Diop‐Christensen, Anna; Pavlopoulos, Dimitris
Abstract : This study investigated the effect of institutions on the unemployment duration gap between non‐EU immigrants and native‐born in 12 European countries. Going further than the existing literature, our study encompassed unemployment duration, distinguishing between exits to inactivity, primary and secondary employment. Additionally, we have provided a stronger micro‐foundation to the comparative literature by introducing institutional measures for unemployment‐related benefits at the individual level rather than merely using aggregate proxies. Our analysis found no disincentive effects of benefits for immigrants. Furthermore, the employment prospects of immigrants were better when the demand for low‐skilled labour was high, and immigration policy was labour market‐oriented. In contrast, employment protection legislation did not affect the unemployment duration of immigrants.